Essential Oil and Ethanolic Extract of Curcuma Inhibits Mammae Tumors in Rats Induction by DMBA - Akhmad Endang Zainal Hasan; Ekowati Handharyani; Sri Wahyuni (Universitas Lambung Mangkurat, 2022)
Curcuminoids and xanthorizol are active components that may act as anticancer in the rhizome of Curcuma xanthorrhiza. The purpose of this study was to determine the content of the class of compounds in curcuma extract and essential oil using the phytochemical screening test method, the Folin-Ciocalteu method to determine the total phenolic content and the AlCl3 method for the total fentuconoid content. In addition, the activity of curcuma in inhibiting the influence of DMBA on the growth of breast cancer in rats was determined. Curcuma extract used is the result of extraction using 70% ethanol on an industrial scale. Total phenolic content and flavonoid extract of curcuma were determined by spectrophotometer. Inhibition testing of tumors formed due to DMBA induction was carried out by administering temulawak extract at doses of 35, 70, 140, 210 and 280 mg/kg body weight. Based on the phytochemical analysis, the ethanol extract of curcuma contained terpenoids, alkaloids, phenolic compounds and flavonoids. The results of the analysis of the ethanol extract of curcuma contained total phenols and flavonoids with concentrations of 42.96 mg GAE/g and 3.96 mg QE/g, respectively. The group that was given curcuma extract as the control group (p<0.05) had a significant difference. Based on the Mann-Whitney analysis, the third group with a dose of 140 mg/kg BW had the highest effect on tumor inhibition. The hope is that the development of curcuma extract into a standardized herbal medicine so that it can be used for the treatment of breast cancer can use the results of this research.